VERBA MODUS JUSIF DALAM AL-QURAN SURAT AL BAQARAH (ANALISIS SINTAKSIS): JUSSIF VERBS IN AL-QURAN SURAH AL BAQARAH (SYNTAX ANALYZE) - Adila, Aprilia Putri; Kuswardono, Singgih; Arifin, Akbar Syamsul (Universitas Negeri Semarang, 2024)
The jusive mode in Arabic is called the jazm mode <الجزم حالة<. The jazm (jusif) mode is characterized by its formal characteristics as a form of derivative or subordinate mode of the indicative mode. Based on initial observations by researchers regarding the jusive mode verbs in the Qur'an Surah Al Baqarah, researchers found a total of 31 data in the first 50 verses and it is suspected that more data will be found until the end of the verses of this letter. The aim of this research is to determine and describe variants of jusive mode verbs and grammatical markers of jusive mode verbs in the Al Qur'an Surah Al Baqarah. This research is qualitative research with a library research research design. The data is in the form of jusive mode verbs with the data source being Al Qur'an Surah Al Baqarah. The instruments used in this research were data cards and recapitulation sheets. The data collection technique uses a pre-considered sampling technique (purposive sampling). The data analysis technique uses the intralingual matching method. The results of this research show 303 data on jusive mode verbs contained in the Qur'an Surah Al Baqarah. From this amount of data, researchers took 104 data samples for analysis. The data is classified based on the jusive mode verb variants and grammatical markers. Based on the jusive mode verb variants, there are three variants of the jusive mode verb, namely (1) Not yet implemented, (2) Conditional, (3) Imperative. Researchers found that 12 data had meaning that had not been implemented, 18 data had conditional meaning, and 74 data had imperative. Based on the grammatical markers, there are three types of grammatical markers for jusive mode verbs, namely (1) Short Vowel Sound Dating, (2) Sound Dating of Words Containing Final Defective Letters, (3) Sound Dating of Words Containing Final Nun Letters. Researchers found 28 data on the dating of short vowel sounds, 13 data on the sound of words containing final defective letters, and 63 data on the sound of words containing final letters.